The benefits and limitations of predicting one repetition maximum using the load-velocity relationship - McBurnie, A. J.; Allen, K. P.; Maybanks, G.; McDwyer, M.; dos Santos, T.; Jones, P. A.; Comfort, P.; McMahon, J. J. (Strength and Conditioning Journal, 2019)
This review aims to provide an overview of the current load-velocity (L-V) approaches and their ability to estimate one-repetition maximum (1RM). The bench press exercise appears to be the most valid and reliable when applying this approach. The ability for L-V relationship to predict 1RM for lower-body lifts remains questionable. Individualized regression equations should be used alongside mean velocity when utilizing this method during the bench press. The 2-point method (2 distinguishable loads, as opposed to multiple loads) and normative velocity data (minimal velocity thresholds at 1RM) may provide a novel and practical way to assess athletes' 1RM.